ETIKA DAN AKUNTABILITAS PELAYAN PUBLIK DALAM TATA KELOLA PEMERINTAH TERKAIT KONSEP “DYNAMIC GOVERNANCE” - Sisman Prasetyo (Department of Public Administration, Faculty of Social and Political Science, Universitas, 2023)
The concept of ethics and accountability of public servants in governance from good governance to dynamic governance is a reference concept that is considered to be able to change government activities properly. Any concept of governance adopted implies to reject various forms of government activities based on authoritarian activities, corruption, collusion, and nepotism that will open up opportunities for other evil acts in carrying out government activities. In this context, dynamic governance becomes central in responding to the challenges faced by the current government so that an innovation related to E-government was born which is an effort to support electronically-based government performance in the context of implementing and improving the quality of services to the community effectively. and efficient The purpose of this paper is to contribute to knowledge by exploring conceptual theoretical and comparing between these concepts from the relevant scientific literature. This paper is a synthesis of qualitative research, using the method of meta-theory (the analysis of theory). This paper attempts to identify some of the existing written evidence regarding the research theme. The results of the study revealed that ethics and accountability of public servants in government governance related to dynamic governance were adopted because of the need to respond to various problems of government activities.